Communication Behaviors to Implement Innovations: How Do AEC Teams Communicate in IPD Projects?. Issue 1 (February 2015) - Sun, Weida; Mollaoglu, Sinem; Miller, Vernon; Manata, Brian
Implementing any innovation successfully is a challenge. In addition to commonly reported climate and values-fit constructs, this study proposes that communication behaviors (i.e., monitoring, challenging, managing, and negotiating) are also vital for innovation implementation. Via an in-depth literature review, the study first defines these metrics. Second, a content analysis of an integrated project delivery (IPD) case study report enables the study to explore if these communication behaviors exist in inter-organizational architecture, engineering, and construction (AEC) project teams. Results provide four key communication metrics for innovation implementation, supported by evidence and examples that illustrate these metrics in AEC teams implementing IPD as an innovation.